Loss of Grin2a causes a transient delay in the electrophysiological maturation of hippocampal parvalbumin interneurons - Chad R. Camp; Anna Vlachos; Chiara Klöckner; Ilona Krey; Tue G. Banke; Nima Shariatzadeh; Sarah M. Ruggiero; Peter Galer; Kristen L. Park; Adam Caccavano; Sarah Kimmel; Xiaoqing Yuan; et al. (Communications Biology, 2023)
Abstract N-methyl-D-aspartate receptors (NMDARs) are ligand-gated ionotropic glutamate receptors that mediate a calcium-permeable component to fast excitatory neurotransmission. NMDARs are heterotetrameric assemblies of two obligate GluN1 subunits (GRIN1) and two GluN2 subunits (GRIN2A-GRIN2D). Sequencing data shows that 43% (297/679) of all currently known NMDAR disease-associated genetic variants are within the GRIN2A gene, which encodes the GluN2A subunit. Here, we show that unlike missense GRIN2A variants, individuals affected with disease-associated null GRIN2A variants demonstrate a transient period of seizure susceptibility that begins during infancy and diminishes near adolescence. We show increased circuit excitability and CA1 pyramidal cell output in juvenile mice of both Grin2a +/− and Grin2a −/− mice. These alterations in somatic spiking are not due to global upregulation of most Grin genes (including Grin2b). Deeper evaluation of the developing CA1 circuit led us to uncover age- and Grin2a gene dosing-dependent transient delays in the electrophysiological maturation programs of parvalbumin (PV) interneurons. We report that Grin2a +/+ mice reach PV cell electrophysiological maturation between the neonatal and juvenile neurodevelopmental timepoints, with Grin2a +/− mice not reaching PV cell electrophysiological maturation until preadolescence, and Grin2a −/− mice not reaching PV cell electrophysiological maturation until adulthood. Overall, these data may represent a molecular mechanism describing the transient nature of seizure susceptibility in disease-associated null GRIN2A patients.